Factors Affecting the Quality of Water - Deivasigamani, Priya; Balakrishnan, Shantakumar; Thamaraikani, Tamilanban (Pharmaceuticals in Water, 2021)
The ground water quality depends on the level of interaction of water and soil, the composition of the recharge water, soil combined with gas and rocks with which the water comes in contact with the unsaturated zone, reactions and the residential time which is taking place inside the aquifer. Henceforth, defined variations could be seen even in the common parts, specifically in the places of rocks of varied compositions and the occurrence of solubility. There are many factors affecting the quality of ground water and surface water. The physical and chemical changes happen to the water which is moving under or over the surface of the land. This type of change is due to either the human activities and/or the natural factors. There are three major factors which are to be considered during the assessment of the quality of water. They are physical factors, chemical factors and biological factors.